(untitled) (International Journal of Engineering and Computer Science, 2014)
In this project the utilization and combining of public key based homomorphic authenticator with random masking to achieve the preservation of privacy to the public cloud data auditing system which meets all the above requirements. If there is a situation for multi auditing tasks then we further extend the technique of bilinear aggregate signature to extend the main result to multi user setting where the third party auditor can perform the multi auditing tasks simultaneously. The main issue is going on, on the outsourced data. Cloud computing produces some of the new and challenging security threats to the cloud users outsourced data. Cloud service providers are the separate entities. The data outsourcing will provide an insecure performance in the user’s outsourced data due to the unauthenticated performance of the strangers. In the existing scenario although the infrastructure of the cloud is good with an powerful computing devices but there were internal and external threats which leads to an issue to the data integrity. The status of the outsourced data was not clear. Although the well infrastructure cloud do not providing the exact status about the users outsourced data.